Disentangling the processes driving plant assemblages in mountain grasslands across spatial scales and environmental gradients. (24th July 2018) - Scherrer, Daniel; Mod, Heidi K.; Pottier, Julien; Litsios‐Dubuis, Anne; Pellissier, Loïc; Vittoz, Pascal; Götzenberger, Lars; Zobel, Martin; Guisan, Antoine
Abstract: Habitat filtering and limiting similarity are well‐documented ecological assembly processes that hierarchically filter species across spatial scales, from a regional pool to local assemblages. However, information on the effects of fine‐scale spatial partitioning of species, working as an additional mechanism of coexistence, on community patterns is much scarcer. In this study, we quantified the importance of fine‐scale spatial partitioning, relative to habitat filtering and limiting similarity in structuring grassland communities in the western Swiss Alps. To do so, 298 vegetation plots (2 m × 2 m) each with five nested subplots (20 cm × 20 cm) were used for trait‐based assembly tests (i.e., comparisons with several alternative null expectations), examining the observed plot and subplot level α ‐diversity (indicating habitat filtering and limiting similarity) and the among‐subplot β ‐diversity of traits (indicating fine‐scale spatial partitioning). We further assessed variations in the detected signatures of these assembly processes along a set of environmental gradients. We found habitat filtering was the dominating assembly process at the plot level with diminished effect at the subplot level, whereas limiting similarity prevailed at the subplot level with weaker average effect at the plot level. Plot‐level limiting similarity was positively correlated with fine‐scale partitioning, suggesting that the trait divergence resulted from a combination of competitive exclusion between functionally similar species and environmental micro‐heterogeneities. Overall, signatures of assembly processes only marginally changed along environmental gradients, but the observed trends were more prominent at the plot than at the subplot scale. Synthesis. Our study emphasises the importance of considering multiple assembly processes and traits simultaneously across spatial scales and environmental gradients to understand the complex drivers of plant community composition. Abstract : By analysing trait patterning in alpine grasslands, we found that at finer spatial scale, limiting similarity was more prominent than habitat filtering. Trait divergence at coarser scale was likely driven by environmental heterogeneity. These findings emphasise the importance of considering multiple assembly processes and traits simultaneously across spatial scales and environmental gradients to understand the complex drivers of plant community composition.